Variabel-variabel yang Memengaruhi Status Multiple Job Holding Pekerja Lansia di Indonesia - Maharami, Aqilla Darrin; Rahani, Rini (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
As economic and social demands increase, many individuals are compelled to take on multiple jobs, a phenomenon known as multiple job holding (MJH). In Indonesia, the rate of multiple job holders has been rising yearly, and the aging population phenomena increases the potential for older workers to take on multiple jobs. While MJH can offer financial benefits, it may also pose significant challenges, particularly for older workers. Although Indonesia records the highest rate of multiple job holders in Southeast Asia, research on this topic remains limited, and no studies specifically focusing on older workers. This study aims to examine the characteristics of older multiple job holders in Indonesia and the variables that affect them. The data used is Sakernas August 2022 microdata, which is analysed descriptively and inferentially using binary logistic regression. The results reveal that 18.16percent of older workers hold multiple jobs. Older workers who tend to have multiple jobs are young elderly, male, married, educated up to primary school, live in rural areas, have shorter working hours in their main job, and work in the informal sector. The high rate of MJH among older workers shows the need for targeted government interventions, such as intensifying school programs for older adults to improve the quality of their competencies and providing social assistance for older adults according to their age.